PENEGAKAN KODE ETIK NOTARIS OLEH DEWAN KEHORMATAN DAERAH DI KABUPATEN SLEMAN - SILALAHI, MICHAEL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study entitled "Notary's Code of Ethics Enforcement by The Regional Board of Honor in Distric Sleman", aims to more determine, asses, and analyze the obstacles being encountered by the Regional Board of Honor in establishing the Code of Ethics in Sleman. This study uses empirical and juridical approach which uses primary an secondary data. The primary data is obtained through interviews while secondary data is collected by literature study. Some notaries who are considered to be able to meer the specified criteria to this study and approved by the Regional Board of Honor are selected for interviews. In addition, interviews are also conducted with the chairman of Indonesian Nottaries Association of Regional Sleman. All data that has been collected is analyzed qualitatively. The result show that the enforcement of the codes of ethics by Regional Board of Honor in District Sleman is not yet properly running. This occurs because of some factors which detain it's performance These factors are the process for imposing sanctions, physchological approach, the quality of imposing sanctions and time and scope of work area which is considered to be too broad. The solution that is possibly done by the Regional Board of Honor in enforcing code of ethics within notaries in Sleman is by monitoring consecutively to provide direction and guidance in the form of conducting meetings once every three months.The Regional Board of Honor is also expected to give oral and/or written sanctions and provide the files of it's imposing. Keywords: Notary, DKD (Regional Board of Honor), Code of Ethics, Enforcement, and District Sleman